Changing Emphases in Innovation Activity: User Innovation - Anna Zaytseva; Olga Shuvalova (Foresight and STI Governance)
Innovation commonly refers to new marketable goods generated by a manufacturer. This concept is the base of the established system of innovation policy. However, a new type of innovation is becoming increasingly widespread — innovation initiated by the user. Such developments are often not based on R&D and technology. Despite the increase in the area of statistical innovation measurement in recent years, the role of the user as an player in innovation is underestimated, both in statistical and political terms.